Energy Efficiency Assessment of the Involvement of an Educational Building using the Prescription Method (RTQ-C) - Spinelli, Rodrigo; Pitol, Alana Francischett; Pasquali, Pedro Henrique Dall’Agnol; Cambeiro, Faustino Patiño; Konrad, Odorico (International Journal of Advanced Engineering Research and Science, 2019)
For a building to be considered sustainable, it is essential that it be energy efficient and assess the impact that its implementation and use will have on the environment. The evaluation of the energy efficiency of the systems that make up a building becomes fundamental. For this, the analysis of the envelope, its materiality, its conductivity indices and thermal transmittance directly influence the energy consumption of a building. Based on the Technical Quality Regulation for the Energy Efficiency Level of Commercial, Service and Public Buildings (RTQ-C), it was possible to evaluate and classify the efficiency levels of an educational building located in the municipality of Lajeado, Rio de Janeiro state. Grande do Sul, Brazil, applying natural and innovative materials for thermal insulation of wraps. The original rating of Level D goes to levels A and B, depending on the amount of insulating material applied. It is noteworthy that for the building to be classified as Level A, it is necessary to reduce the energy consumption of the artificial lighting system by 65%.